Socioeconomic Transformation and the Resulting Settlement Segregation in a Historic Kampong in Semarang City - Pradoto, Wisnu; Angelita, Emanuella Clara; Ma'rif, Samsul (Department of Urban and Regional Planning, Universitas Diponegoro, 2025)
Segregation and migration are urbanization phenomena that are visible in settlements. Motivation to move in or move out which is influenced by socio-economic characteristics is the main factor that changes the neighborhood pattern. This research aims to explain the segregation which is driven by socio-economic transformation and migration in a historic kampong that has ethnic, racial and religious diversity in the city center. Entropy index analysis is used to calculate the level of segregation, while migration motivations and residence preferences that form clusters are explored through interviews. Field observations were carried out to map segregation patterns. The study results show that segregation is influenced by social and economic factors, not religion, race or ethnicity. The afluent young generation tends to separate between working place and living home, but their ancestors loved to live and work in the same place as social contact is worth to them. Social value changes from generation to generation. The low-income migrants show differently. They are clustering due to their origin. Social contact with the community is much more important and makes them secured.